Some observations on classroom teaching innovations at the elementary school level in Japan - Tablante, Isabel L.
The impressive and spectacular innovations in elementary education in a highly developed nation like Japan are still a dream to a developing countries of the region, including the Philippines-a dream that certainly unattainable. They serve as a goal worth aspiring for, an inspiration and a challenge to educators, policymakers and citizens at large, in a country like the Philippines where educational development occupies a strategic place in the task of nation-building.
Keywords: Education, Elementary -- Japan; Teaching -- Japan -- Aids and devices; Educational innovations -- Japan